The effect of microfinance institutions’ products on financial performance of small and medium enterprises: A case of Machakos Town, Kenya - Omwansa, David Masini (My University, 2015)
Vision 2030 has emphasized the importance of SMEs in Kenya. Small and Medium Enterprises are noted as a crucial catalyst for achieving vision 2030. The research was done on the effects of Microfinance institutions` on financial performance of small and medium enterprises in Machakos town, where the general objective of the research was to determine whether there was any significant effect of Microfinance institutions` products on the financial performance of small and medium enterprises in Machakos town. Descriptive research design was employed since the researcher collected information through descriptions and this design is also useful for identifying variables and hypothetical construction. Stratified random sampling technique was used, and the sample size was determined as 372, at 95% confidence interval. Primary data was collected through questionnaires issued to the owners and managers of SMEs, while secondary data was collected by use of secondary data collection sheet. Both descriptive and inferential statistics were used to analyze data, while correlation and regression were also used to establish the strength of the relationship between microfinance products and financial performance of small and medium enterprises. Statistical Packages for Social Sciences (SPSS) was used by the researcher to facilitate the analysis and interpretation of data, and the results obtained was presented by the use of bar graphs, pie charts, and table for easy interpretation. The results showed that, the MFIs` products offered (micro savings, micro credit and training) had a strong positive correlation on the financial performance of the SMEs, while there was a weak positive correlation between micro insurance and financial performance of the SMEs. The regression analysis indicated that; micro savings, micro credit and micro insurance had significance effect on the financial performance of SMEs, while training had no significance effect on the financial performance of the SMEs. The study recommended that MFIs have a great responsibility of ensuring the proper use of credit which is an important facility in financial performance of businesses. To achieve this, credits should be SMEs-oriented and not product- oriented. Proper and extensive monitoring activities should be provided to SMEs who are granted the micro credit product. MFIs can research into very profitable business lines and offer credit to SMEs who have the capacity to exploit such business lines, micro insurance is paramount to SMEs in cushioning them in the event of unfavorable occurrence, and should be enhanced properly to the SMEs, and that business and financial training should be provided by MFIs on a regular basis and most cases should be tailored toward the training needs of the SMEs.